Solve for: 414 Request-URI Too Large

Expression: $$\left. \begin{array} { l } { \quad 2 ( n - 1 ) + 4 n = 2 ( 3 n - 1 ) } \end{array} \right.$$

Use the distributive property to multiply $2$ by $n-1$.

$$2n-2+4n=2\left(3n-1\right)$$

Combine $2n$ and $4n$ to get $6n$.

$$6n-2=2\left(3n-1\right)$$

Use the distributive property to multiply $2$ by $3n-1$.

$$6n-2=6n-2$$

Subtract $6n$ from both sides.

$$6n-2-6n=-2$$

Combine $6n$ and $-6n$ to get $0$.

$$-2=-2$$

Compare $-2$ and $-2$.

$$\text{true}$$

This is true for any $n$.

$$n\in \mathrm{R}$$